2008
DOI: 10.1086/533419
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy and Central Nervous System HIV Type 1 Infection

Abstract: Central nervous system (CNS) human immunodeficiency virus type 1 (HIV-1) infection begins during primary viremia and continues throughout the course of untreated systemic infection. Although frequently accompanied by local inflammatory reactions detectable in cerebrospinal fluid (CSF), CNS HIV-1 infection usually is not clinically apparent. In a minority of patients, CNS HIV-1 infection evolves into encephalitis during the late stages of systemic infection, which compromises brain function and presents clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 119 publications
2
87
0
1
Order By: Relevance
“…Unexpectedly, in the patients with systemic treatment failure in Fig. 1(C) (plasma VL>50 copies/mL), while many of the CSF VLs were detected, the difference between CSF and plasma increased to nearly 2 logs, i.e., CSF was proportionally more suppressed than plasma in these patients with drug resistance and reduced adherence [14]. Figure 1(D) shows findings in patients with neurosymptomatic escape that will be discussed later that contrast markedly with these more common relationships in treated patients.…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 84%
See 2 more Smart Citations
“…Unexpectedly, in the patients with systemic treatment failure in Fig. 1(C) (plasma VL>50 copies/mL), while many of the CSF VLs were detected, the difference between CSF and plasma increased to nearly 2 logs, i.e., CSF was proportionally more suppressed than plasma in these patients with drug resistance and reduced adherence [14]. Figure 1(D) shows findings in patients with neurosymptomatic escape that will be discussed later that contrast markedly with these more common relationships in treated patients.…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 84%
“…Figure 1 illustrates the relationship of CSF to plasma HIV in four clinical settings, and Fig. 1(A) uses previously published data from untreated patients [14] to illustrate this relationship. As with systemic infection, CNS virus populations also evolve within the individual infected host and may change importantly as systemic disease progresses [15,16,13].…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs in 30-50% of patients, depending on both the cohort under study and how the impairment is identified [1][2][3][4][5][6][7][8]. The current diagnostic approach is descriptive: HIV-associated neurocognitive disorder (HAND) is termed 'asymptomatic neurocognitive impairment' when found on testing in the absence of symptoms, and 'mild neurocognitive disorder' when both signs and symptoms are present, but are not severe enough to constitute frank dementia [9].…”
Section: Introductionmentioning
confidence: 99%
“…HIV-Patienten mit einem initial schlechten Immunstatus (niedrige CD4-Zellzahlen), der sich unter cART verbesserte, waren einige Jahre nach cART-Beginn kognitiv noch gering schlechter als HIV-Negative, mit teilweise allerdings weiterer kognitiver Besserung im Verlauf [69]. Während somit schwere Ausprägun-gen von HAND, wie sie vor der cART-Ära üblich waren, bei antiretroviral behandelten Patienten nun selten sind [84], werden in der klinischen Praxis leichtere kognitive Störungen beobachtet, die zudem in früheren Infektionsstadien auftreten [49,50,92].…”
Section: » Hand Tritt Heute Häufiger In Früheren Stadien Auf Und Zeigunclassified